KUALITAS PELAYANAN TIKET DI PT. NABILA HOLIDAY TOUR AND TRAVEL PEKANBARU - Citra Sakinah Marloni; Andi M Rifiyan Arief (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This reasearch is to know how the ticket service quality at PT. Nabila Holiday Tour and Travel Pekanbaru. This research uses a descriptive quantitative method to describe the real state by collecting existing data field. The sample in this reasearch as many as 100 responden were taken using accidental sampling. While data collection techniques in this reasearch use observation, questionnaires, interviews. By using a Likert scale as a measuring instrument determines the length of the short interval. Based on field research that has been done, the results in the can is about ticket quality service at PT. Nabila Holiday Tour and Travel Pekanbaru included in the category good enough and not in accordance with the vision and mission of the company.Key words : Quality, Service, Flight Ticket